1990
DOI: 10.1017/s000156600000564x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variance and Heritability of Serum Cholesterol and Triglycerides Among Chinese Twin Neonates

Abstract: In order to examine the genetic variance and heritability of serum total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and triglycerides, a total of 349 pairs of same-sexed twin neonates born in four major general teaching hospitals in Taipei City were studied. Based on the placental pattern and 12 red blood cell antigens, 271 monozygotic (MZ) and 78 dizygotic (DZ) twin pairs were identified. There was a significant genetic variance for total cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Corey et al [12] found that the variance of total plasma cholesterol in cord blood, which has a higher percentage of HDL-C than in adults, was significantly greater in dichorionic MZ twins than in the cord blood of monochorionic MZ twins. Chen et al [9] reported slightly higher, but nonsignificant within-pair differences in cord blood HDL-C and total cholesterol in dichorionic vs monochorionic MZ twins. Greater variance of dichorionic than monochorionic twins could account for the greater DZ than MZ variance in the NHLBI twins because all DZ twins are dichorionic and only one-third of MZ twins are dichorionic [8].…”
Section: Introductionmentioning
confidence: 94%
“…Corey et al [12] found that the variance of total plasma cholesterol in cord blood, which has a higher percentage of HDL-C than in adults, was significantly greater in dichorionic MZ twins than in the cord blood of monochorionic MZ twins. Chen et al [9] reported slightly higher, but nonsignificant within-pair differences in cord blood HDL-C and total cholesterol in dichorionic vs monochorionic MZ twins. Greater variance of dichorionic than monochorionic twins could account for the greater DZ than MZ variance in the NHLBI twins because all DZ twins are dichorionic and only one-third of MZ twins are dichorionic [8].…”
Section: Introductionmentioning
confidence: 94%